The Search of Recognition in the Formation of Political Identities. Latin America’s Ambiguous Position facing Western Modernity and the Construction of National Consciousness - Mansilla, H. C. F. (Nómadas. Critical Journal of Social and Juridical Science, 2013)
The text is based on the recognition theory by Axel Honneth and on the critical analyses of romanticism (as a philosophy) in order to understand the complex relationship of Latin American societies with western modernity. Romantic conceptions are seen as an early and clairvoyant critique of modern alienations. In Latin America romantic tendencies have also served for revaluating the past and the own traditions in front of the cultural weight of western modernity. Latin American tradition of essays is perceived as a very interesting answer to Latin America’s lack of recognition in the concert of nations. Some currents of the Latin American essays are, however, under antiliberal influence and are inclined to justify populist and authoritarian regimes.
Keywords: antiliberalism; discrimination; essay; Latin America; recognition; romanticism